Genetic Diversity and Molecular Evolution of a Violaxanthin De-epoxidase Gene in Maize - Xu, Jing; Li, Zhigang; Yang, Haorui; Yang, Xiaohong; Chen, Cuixia; Li, Hui (Frontiers in Genetics, 2016)
Violaxanthin de-epoxidase (VDE) has a critical role in the carotenoid biosynthesis pathway, which is involved in protecting the photosynthesis apparatus from damage caused by excessive light. Here, a VDE gene in maize, ZmVDE1, was cloned and shown to have functional domains in common with the gramineous VDE protein. Candidate gene association analysis indicated that no polymorphic sites in ZmVDE1 were significant association with any of the examined carotenoid-related traits at P = 0.05 in an association panel containing 155 maize inbred lines. Nucleotide diversity analysis of VDE1 in maize and teosinte indicated that its exon had less genetic variation, consistent with the conserved function of VDE1 in plants. In addition, dramatically reduced nucleotide diversity, fewer haplotypes and a significantly negative parameter deviation for Tajima’s D test of ZmVDE1 in maize and teosinte suggested that a potential selective force had acted across the ZmVDE1 locus. We further identified a 4.2 Mb selective sweep with low recombination surrounding the ZmVDE1 locus that resulted in severely reduced nucleotide diversity on chromosome 2. Collectively, natural selection and the conserved domains of ZmVDE1 might show an important role in the xanthophyll cycle of the carotenoid biosynthesis pathway.